Thymic Epithelial Cell-Derived IL-15 and IL-15 Receptor α Chain Foster Local Environment for Type 1 Innate Like T Cell Development - Tao, Huishan; Li, Lei; Liao, Nan-Shih; Schluns, Kimberly S.; Luckhart, Shirley; Sleasman, John W.; Zhong, Xiao-Ping (Frontiers in Immunology, 2021)
Expression of tissue-restricted antigens (TRAs) in thymic epithelial cells (TECs) ensures negative selection of highly self-reactive T cells to establish central tolerance. Whether some of these TRAs could exert their canonical biological functions to shape thymic environment to regulate T cell development is unclear. Analyses of publicly available databases have revealed expression of transcripts at various levels of many cytokines and cytokine receptors such as IL15, IL15Ra, IL13, and IL23a in both human and mouse TECs. Ablation of either IL15 or IL15Ra in TECs selectively impairs type 1 innate like T cell, such as iNKT1 and gdT1 cell, development in the thymus, indicating that TECs not only serve as an important source of IL15 but also trans-present IL15 to ensure type 1 innate like T cell development. Our data indicate that some TRAs may perform due roles as self-antigens to trigger negative selection and as biologically active molecules to shape thymic environment. Because type 1 innate like T cells are proinflammatory and contribute to adipogenesis, our data suggest the possibility that TEC may intrinsically control thymic inflammatory innate like T cells to influence thymic environment and ultimately age-associated thymic involution.